Producing the Past: The Changing Protagonists of Canadian Heritage. Issue 6 (7th November 2022) - Gunter, Christopher; Nelson, Robin
Abstract: The Canadian private sector also contributes to the heritage commemoration landscape by working with the government and accessing support programs. Arguably, one of the most impactful contemporary examples of the private sector's heritage commemoration involvement are the Heritage Minutes (Minutes), which are sixty-second videos depicting historical narratives of events and people from Canadian history. Given their notoriety, the production and story selections for each Minute raises questions about the Canadian heritage landscape: who and what is represented or missing, and what are the implications? By examining these questions, this article aims to hold these Minutes—financed and authorized by government—to account and to understand what themes and messages these vignettes aim to impart on and authorize as 'commemorative worthy' to the Canadian public. This article focuses on examining the Minutes and documenting their thematic trends with a specific emphasis on identifying how marginalized groups are represented in the Minutes.